Assessing Leak Paths in the Cement Sheath of a Cased Borehole by Analysis of Monopole Wavefield Modes (Communications in Computational Physics, 2020)
Evaluation of possible leakage pathways of CO2 injected into geological formations for storage is essential for successful Carbon Capture and Storage (CCS). Achannel in the borehole cement, which secures the borehole casing to the formation,may allow CO2 to escape. Risk assessment and remediation decisions about the presence of such channels depend on channel parameters: radial position $r$ from the centerof the borehole; channel thickness $d$; azimuthal position $φ$ of the channel; and azimuthal extent $θ$ of the channel. Current state-of-the-art cement-bond logging technology, which uses only the first arrival at a centralized borehole receiver, can diagnoselimited details about CO2 leak channels. To accurately characterize the possible leakpaths in the cement, we use a 3-dimensional finite-difference method to investigate theuse of the abundant data collected by a modernized monopole sonic tool that containsan array of azimuthally distributed receivers. We also investigate how to improve thetool design to acquire even more useful information. For cases where borehole fluidis either water or supercritical CO2, we investigate various receiver geometries, multimodal analyses of multi-frequency data to discover the type of logging tool that provides the best information for CCS management. We find that an appropriate choiceof wave modes, source frequencies, source polarities, and receiver locations and offsets provides sensitivity to $d$, $φ$, $θ$. The amplitude of the first arrival from a monopolesource is sensitive to $θ$. Amplitudes at receivers at different azimuths are sensitive to $φ$. The slow Stoneley mode (ST2) velocity is sensitive to $d$, but ST2 is not easy to pickwhen $θ$ and $d$ are small. Further improvement is necessary to provide comprehensiveinformation about possible flow channels in casing cement.